Protective effect of methanolic extract of Berberis integerrima Bunge. root on carbon tetrachloride-induced testicular injury in Wistar rats - Fereshteh Rafiee; Vahid Nejati; Reza Heidari; Hossein Ashraf (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Tissue protective effect of compounds with antioxidant properties has been demonstrated. The alkaloids found in barberry root are considered as antioxidants. Objective: According to barberry protective effects in different tissues, in this study, the protective effect of Berberis integerrima Bge. root (MEBIR) was evaluated against CCl4-induced testicular damages in Wistar rats. Materials and Methods: 40 mature male rats were randomly divided into 5 groups: 1: Normal control, 2: Sham: received CCl4 diluted in olive oil (50% v/v; 1ml/kg bw), intraperitoneally, twice a week for 4 weeks, 3 and 4: Sham rats treated with MEBIR (250 and 500 mg/kg bw) for 28 days, 5: Sham rats treated with silymarin (50 mg/kg bw) for 28 days. After 28 days, serum testosterone level, absolute testis weight, catalase activity, malondialdehyde level, and histological parameters were investigated. Results: In the treated rats with MEBIR (250 and 500 mg/kg bw) or silymarin (50 mg/kg bw), there was a significant increase in the absolute testis weight, testosterone level, seminiferous tubules diameter (p<0.001), thickness of the epithelium, tubule differentiation index (p<0.001), spermiogenesis index (p<0.001), the activity of catalase, and a significant decrease in interstitial tissue thickness (p<0.001) and malondialdehyde level in comparison with CCl4-treated group. The effect of the MEBIR at dose of 500 mg/kg bw is more than that of the standard drug, silymarin (50 mg/kg bw). Conclusion: From the results, it is suggested that the protective effects of MEBIR is possibly due to antioxidant effects of its bioactive compounds.